FFCD 1709-SIRTCI phase II trial: Selective internal radiation therapy plus Xelox, Bevacizumab and Atezolizumab in liver-dominant metastatic colorectal cancer. Issue 7 (July 2022) - Randrian, Violaine; Pernot, Simon; Le Malicot, Karine; Catena, Vittorio; Baumgaertner, Isabelle; Tacher, Vania; Forestier, Julien; Hautefeuille, Vincent; Tabouret-Viaud, Claire; Gagnaire, Alice; Mitry, Emmanuel; Guiu, Boris; et al.
Abstract: Immune checkpoint inhibitors (ICI) have high efficacy in metastatic colorectal cancer (mCRC) with microsatellite instability (MSI) but not in microsatellite stable (MSS) tumour due to the low tumour mutational burden. Selective internal radiation therapy (SIRT) could enhance neoantigen production thus triggering systemic anti-tumoral immune response (abscopal effect). In addition, Oxalipatin can induce immunogenic cell death and Bevacizumab can decrease the exhaustion of tumour infiltrating lymphocyte. In combination, these treatments could act synergistically to sensitize MSS mCRCs to ICI SIRTCI is a prospective, multicentre, open-label, phase II, non-comparative single-arm study evaluating the efficacy and safety of SIRT plus Xelox, Bevacizumab and Atezolizumab (anti-programmed death-ligand 1) in patients with liver-dominant MSS mCRC. The primary objective is progression-free survival at 9 months. The main inclusion criteria are patients with MSS mCRC with liver-dominant disease, initially unresectable disease and with no prior oncologic treatment for metastatic disease. The trial started in November 2020 and has included 10 out of the 52 planned patients.